2019
DOI: 10.1002/qre.2593
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic probability control limits for CUSUM charts for monitoring proportions with time‐varying sample sizes

Abstract: We consider the problem of monitoring a proportion with time‐varying sample sizes. Control charts are generally designed by assuming a fixed sample size or a priori knowledge of a sample size probability distribution. Sometimes, it is not possible to know, or accurately estimate, a sample size distribution or the distribution may change over time. An improper assumption for the sample size distribution could lead to undesirable performance of the control chart. To handle this problem, we propose the use of dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
(23 reference statements)
1
6
0
Order By: Relevance
“…Moreover, we introduce the CUSUM chart (cumulative sum control chart) as another state-of-the-art algorithm in this experiment. CUSUM has excellent performance in change point detection issues [35,36], which are similar with our problem. We use a similar strategy using SVM as the basic classifier and CUSUM as the transition activity recognition method.…”
Section: Experiments 3: Overall Performancesupporting
confidence: 68%
“…Moreover, we introduce the CUSUM chart (cumulative sum control chart) as another state-of-the-art algorithm in this experiment. CUSUM has excellent performance in change point detection issues [35,36], which are similar with our problem. We use a similar strategy using SVM as the basic classifier and CUSUM as the transition activity recognition method.…”
Section: Experiments 3: Overall Performancesupporting
confidence: 68%
“…Using simulation or other numerical methods to control the conditional false alarm rate (CFAR) has proven very useful in designing control charts, especially when a covariate varies over time. Recent examples accounting for varying sample sizes include Aytaçoğlu and Woodall, 1 who used the CFAR to determine control limits for the cumulative sum (CUSUM) chart for monitoring proportions, and Aytaçoğlu et al 2 . who used this dynamic control limit approach to design the multivariate exponentially weighted moving average (MEWMA) chart.…”
Section: Introductionmentioning
confidence: 99%
“…The CFAR at a given time is the probability of a false alarm given no previous false alarm. Recent studies by Aytaçoğlu and Woodall, 1 Aytaçoğlu et al, 2 and Aytaçoğlu et al 3 have demonstrated the effectiveness of this approach in designing the binomial cumulative sum, the multivariate exponentially weighted moving average (EWMA), and the adaptive EWMA charts, respectively, while accommodating varying sample sizes. More related works in this direction are Shen et al, 4 Zhang and Woodall, 5 Huang et al, 6 Zhang and Woodall, 7 and Driscoll et al, 8 to name a few.…”
Section: Introductionmentioning
confidence: 99%